Meningkatkan Keterampilan Berbicara Bahasa Jawa Ngoko Melalui Model Pembelajaran Kooperatif Teknik Bercerita Berpasangan pada Siswa Kelas IV SD Negeri 1 Kedungbanteng - Anis Marfungah; Okto Wijayanti; Arifin Muslim (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
The aim of this research was to improve Javanese Ngoko speaking skill of grade IV students of SD Negeri 1 Kedungbanteng through the implementation of paired storytelling technique. This was a Classroom Action Research. This research was conducted collaboratively with the teacher of grade IV of SD Negeri 1 Kedungbanteng. This research was conducted in two cycles which consisted of 4 meetings. Each cycle covered the stages of planning, treatment, observation, and reflection. The subjects of this research were 20 students of grade IV of SD Negeri 1 Kedungbanteng. The source of the data was grade IV students of SD Negeri 1 Kedungbanteng. The data were collected through spoken tests. The results of the research revealed that awell-implemented of paired storytelling learning technique can improve grade IV students' Javanese Ngoko speaking skill, especially about puppet stories. It was viewed by the improvement of learning in each cycle. The students' learning achievement on Javanese Ngoko speaking skill under the material of puppet stories in cycle Iwas 68.56% and in cycle II was 84.03%. The main obstacle in implementing the paired storytelling technique isthat the students were not used to speak using Javanese Ngoko, especially during the Javanese learning activities. Finally, it could be concluded that a well-implemented of paired storytelling technique could improvethe Javanese Ngoko speaking skill about puppet stories of grade IV students of SD Negeri 1 Kedungbanteng.